Tecnologia educacional aplicada na escola tecnica de ensino médio Rubens de Faria e Souza - Fonseca, José Rosa da (2014)
This research studies the existing technologies that can be used in education and what these technologies are used in the Escola Técnica Estadual Rubens de Faria e Souza, located in Sorocaba-SP, in teaching technical courses in its curriculum. A study on the evolution of technology in education drawing on the work carried out by researchers and educators, which is explained the difference between the concepts of automating and computerizing education was developed. For better understanding of the research was developed in the history of computing in education in Brazil, using as a basis for this research Laws Guidelines imposed by government agencies. It is described on technical education, its history and its importance throughout the history of the country, and as the keeper of the chosen school operates within the State of São Paulo. The study done by the data collected, the Guidelines cited, the work carried out by researchers and educators, we can see that there is a line of thought with regard to the actual use of technologies that part of the teachers use them only as a means of improving the appearance of their classes, and not to increase the development of knowledge by students, and some reasons given for this situation is the lack of financial investment, the allegation of lack of time and stimulation to meet the actual use of these technologies by both institutions, as even some teachers. For more specific details on the use of technology within the technical school was chosen Mechanical technician course. Through the study of the lesson plans, the site content and other information gathered was made a qualitative and quantitative survey of technologies available and used for the course, in which we can conclude that the teachers use the resources available, but appropriately in the functions of these resources